2016
DOI: 10.1002/cncr.30146
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in survival among patients with advanced renal cell carcinoma in the targeted therapy era

Abstract: Background African American (AA) patients with renal cell cancer (RCC) have historically had inferior survival compared to Caucasian patients. Recent studies suggest the survival disparity between races may be worsening since the advent of targeted therapies for RCC. This study examines survival rates of AA and Caucasian patients with advanced RCC over time to determine if a disparity in survival persists in the targeted therapy era. Methods We identified patients with stage IV RCC in the National Cancer Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…A recent study also showed that blacks and Hispanics were less likely and Asians more likely than whites to receive EGFR testing (8). Racial disparities in cancer treatment have been well documented (15)(16)(17)(18); with respect to targeted therapy treatments in particular, it has been found that black patients are less likely than white patients to receive HER2-targeted therapies for breast cancer (19), and black patients with renal cancer show worse survival than whites even after the advent of targeted therapy based on VEGF inhibition (20,21). Despite these studies on disparities in cancer treatment, little is known about whether such discrepancies are stable, growing, or shrinking over time within the context of the rapidly evolving and relatively new field of precision cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed that blacks and Hispanics were less likely and Asians more likely than whites to receive EGFR testing (8). Racial disparities in cancer treatment have been well documented (15)(16)(17)(18); with respect to targeted therapy treatments in particular, it has been found that black patients are less likely than white patients to receive HER2-targeted therapies for breast cancer (19), and black patients with renal cancer show worse survival than whites even after the advent of targeted therapy based on VEGF inhibition (20,21). Despite these studies on disparities in cancer treatment, little is known about whether such discrepancies are stable, growing, or shrinking over time within the context of the rapidly evolving and relatively new field of precision cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, not all patients have equal access to recommended follow‐up clinical care, neuroimaging, and salvage treatment. Disparities in access to cancer care among different racial and socioeconomic groups are well recognized in the medical literature . The effect of disparities in access to care on patient outcomes is unknown when a strategy of treating brain metastases with SRS alone is used.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in access to cancer care among different racial and socioeconomic groups are well recognized in the medical literature. [6][7][8][9][10][11][12][13] The effect of disparities in access to care on patient outcomes is unknown when a strategy of treating brain metastases with SRS alone is used. We compared clinical outcomes between safety-net hospital (SNH) and private hospital (PH) patients treated with SRS alone to test the hypothesis that, because of worse neurologic outcomes, SRS alone with observation may not always be suitable for patients originating from an SNH environment who may have barriers to appropriate follow-up care.…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the thoughtful comments by Grant et al on vitamin D status as a possible etiology for the observed racial disparity in survival between African American and white patients with advanced renal cell carcinoma in our analysis . Although the National Cancer Database is a powerful tool for performing disparity and outcomes research, it has limitations and specifically does not include information on serum 25‐hydroxyvitamin D levels, so we were unable to include 25‐hydroxyvitamin D as a covariate in our analysis.…”
mentioning
confidence: 99%